Creating a learning environment in your practice or facility - Bob Mash; Jill Edwards (South African Family Practice)
Family physicians are expected to build the capacity of the primary care team and to provide clinical training to students, but often lack the educational expertise and a supportive learning environment. This article aims to outline the competencies needed to fulfil these expectations and to assist with professional development in this area. The organisational environment has a profound effect on the success of learning and issues such as adequate infrastructure, optimal staff numbers and mix, appropriate patient mix, quality of care, supportive management and organisational culture are all important. Within this organisational culture learning is often dependent on an effective clinical trainer. Clinical trainers impact learning through role modelling, facilitation of learning and providing up to date information. They need educational competencies to embed brief and effective training into clinical practice, to provide effective feedback and to engage with small group teaching and assessment. The family physician can lead the entire team and practice through developing themselves as a clinical trainer, creating supportive relationships and transforming policies and processes to support innovation and learning.